From Anecdote to Formal Evaluation: Reflections from More Than Two Decades on the Local Food Research Trail at USDA - Tropp, Debra (Journal of agriculture, food systems, and community development, 2019)
Introduction In the waning days of my career at the U.S. Department of Agriculture (USDA), the editors of this journal encouraged me to share some reflections about the evolution of local food research and data collection during the past two decades, and I am deeply appreciative for the opportunity. It has been my great fortune to have witnessed the extraordinary transformation of the local food sector firsthand since the mid-1990s. What started out as a minor assignment to oversee a single-and eventually unsuccessful-cooperative research agreement on school food procurement with the Georgia Department of Agriculture in 1995 ended up piquing my interest about the opportunity for growth in local food sales within institutional and commercial food service, as well as retail channels. This subject has remained the primary focus of my professional life and a subject of vast curiosity for me ever since. For someone like me, who has been immersed in the world of local food systems for more than 20 years, it is staggering-and gratifying-to consider both the profound changes in research and data availability that have occurred over the course of my career, and the multiplicity of ways that relevant evidence and data can now be employed to guide business and community development through local food system expansion. My intent in this article is to briefly examine the chronological history of local food research at USDA as I experienced it "in the trenches," and observe the combination of Congressional mandate, political influence, personal curiosity, and, sometimes, pure serendipity that permitted this body of work to emerge.